Staging Neck Dissection and Transoral Robotic Surgery Treatment Algorithm in Palatine Tonsil Cancer. (March 2018) - Spellman, Joseph; Sload, Ryan; Kim, Paul; Martin, Peter; Calzada, Gabriel
Objective: This study introduces a treatment algorithm based on staging neck dissection to identify patients with palatine tonsil squamous cell carcinoma who can be effectively treated with single-modality transoral robotic surgery while maintaining quality of life. Study Design: Retrospective case series. Setting: Kaiser Permanente Southern California Medical Group from 2012 to 2017. Subjects and Methods: Patients with early-stage (T1/2) palatine tonsil squamous cell carcinoma with clinically and radiographically N0 necks underwent staging neck dissection. Those with pN2/3 disease or extracapsular extension on final pathology were triaged to definitive chemoradiation treatment. Patients with confirmed pN0/1 necks without extracapsular extension were treated definitively with transoral robotic surgery. Results: Nineteen patients with cN0 disease underwent selective neck dissection. All were p16 positive. Of these, 14 had pathologically confirmed N0/1 necks without extracapsular extension and were treated with primary surgical resection via transoral robotic surgery. Clear margins were obtained on all patients. There were no significant intra- or postoperative complications. No patients required gastrostomy tube or tracheostomy placement. Mean and median follow-up was 28 months with no recurrences to date. Conclusion: Up-front staging neck dissection accurately triages low-risk patients, determining candidates for single-modality definitive treatment with transoral robotic surgery. This approach provides excellent survival outcomes and minimal morbidity and maintains quality of life among appropriately selected patients with palatine tonsil cancer.